ISOLATION AND IDENTIFICATION OF BARTONELLA SPP. FROM BAT BLOOD AT TANJUNG RINGGIT CAVE ON EAST LOMBOK - Andreyani Attamimi; Rima Nurmayani; Erni; Kunti Tirtasari; Kholik (SANGKAREANG, 2018)
Many research explained that bats are an important reservoir for Bartonella spp. On Lombok Island has many caves for breeding house of bats. The purpose of this research is to isolate and identify Bartonella spp. at Tanjung Ringgit Cave on East Lombok. An Observational survey with explorative laboratory was carried out on Tanjung Ringgit bat cave during May 2018. The bats were captured by net trap and blood samples were collected by puncturing the axillaries vein of bats for blood smears and examination of the presence of intraerythrocytic corpuscles. Each of blood samples was dipped in sterile BHI and they were incubated over the night. After 24 hours the samples were inoculated in Blood Agar under aerobic conditions at Laboratory of Public Health and calibration, Province of Nusa Tenggara Barat. The colonies were purified and characterized by biochemical methods. The result of blood smears by showed that 3 (30%) of 10 bat blood samples were found intraerythrocytic corpuscles. The morphological colonies of bacteria of the three bat blood that found intraerythrocytic corpuscles on Blood Agar are Heterogenic colonies, small regular to irregular larger forms and No hemolysis on blood agar. The result of the biochemical test showed that bacteria was non fermentative, urease, and indole negative. It also did not utilize citrate and Triple Sugar Iron (TSI) showed alkaline. Bartonella-like was isolated from bat blood at Tanjung Ringgit Cave on East Lombok besides on blood smears examination, The morphological colonies on Blood Agar and biochemical test of isolated bacteria of this research.